Empowering Teachers in Academic Publication through Community-Based Mentorship and Participatory Appraisal - Utomo, Asep Purwo Yudi; Isnarto, Isnarto; Pramono, Didi; Kesuma, Rossi Galih; Yanitama, Arka; Puspita, Maria Ayu; Widhiyanto, Riyadi; Islamy, Amilia Buana Dewi; Maharani, Annisa Tetty (Universitas Negeri Semarang, 2024)
This community service project aims to empower teachers in Semarang City to improve their skills in academic writing and publication through a community-based mentorship program. The project addresses critical challenges faced by teachers, including limited time for research, lack of experience in scientific publication, and funding constraints. Using the Participatory Community Appraisal (PCA) method, the program was designed to actively involve teachers in planning, executing, and evaluating the mentorship activities. The community of teachers, particularly those involved in the PKY (Pengembang Konten Youtube) Teacher Community, received intensive training and guidance in scientific writing, article submission, and publication processes. The project results include a significant improvement in teachers' academic writing abilities, with several articles prepared for submission to national journals. The collaborative approach fostered a sense of ownership among participants, making the outcomes more sustainable. This initiative highlights the importance of providing structured mentorship to enhance teachers' professional development and their contributions to academic knowledge.